Measuring collaboration and communication to increase implementation of evidence-based practices: the cultural exchange inventory. (14th February 2018) - Palinkas, Lawrence A; Garcia, Antonio; Aarons, Gregory; Finno-Velasquez, Megan; Fuentes, Dahlia; Holloway, Ian; Chamberlain, Patricia
Abstract : The Cultural Exchange Inventory (CEI) is a 15-item instrument designed to measure the process (7 items) and outcomes (8 items) of exchanges of knowledge, attitudes and practices between members of different organisations collaborating in implementing evidence-based practice. We conducted principal axis factor analyses and parallel analyses of data describing exchanges with intermediary organisations, treatment developers, other agencies in the same county, and agencies in other counties of 105 leaders of county youth-serving systems in California and Ohio participating in a randomised controlled trial of the effectiveness of community development teams in scaling up the use of an evidence-based practice for treatment of youth in foster care. The CEI scale demonstrates strong internal consistency and convergent and discriminant validity, and shows potential in understanding the role of cultural exchanges in evidence-based practice implementation.